Isocyanide Reactions Toward the Synthesis of 3-(Oxazol-5-yl)Quinoline-2-Carboxamides and 5-(2-Tosylquinolin-3-yl)Oxazole - Yasaei, Zahra; Mohammadpour, Zeinab; Shiri, Morteza; Tanbakouchian, Zahra; Fazelzadeh, Shima (Frontiers in Chemistry, 2019)
A palladium-catalyzed three-component reaction between 5-(2-chloroquinolin-3-yl)oxazoles, isocyanides, and water to yield 3-(oxazol-5-yl)quinoline-2-carboxamides is described. Interestingly, sulfonylation occurred when the same reaction was performed with toluenesulfonylmethyl isocyanide (TosMIC) as an isocyanide source. The reaction with 5-(2-chloroquinolin-3-yl)oxazoles and TosMIC in the presence of Cs2CO3 in DMSO afforded 5-(2-Tosylquinolin-3-yl)oxazoles. In basic media, TosMIC probably decomposed to generate Ts- species, which were replaced with Cl-. Tandem oxazole formation with subsequent sulfonylation of 2-chloroquinoline-3-carbaldehydes to form directly 5-(2-tosylquinolin-3-yl)oxazoles was also investigated.